2015
DOI: 10.1097/prs.0000000000001263
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Role of Columellar Strut Graft in Primary Open Approach Rhinoplasty

Abstract: In primary open approach rhinoplasty, if native anatomical support structures of the nasal tip are preserved or reconstructed, preoperative goals regarding nasal tip projection, nasal profile proportions, and columellar integrity can be consistently achieved without using columellar strut grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 2 publications
1
20
0
Order By: Relevance
“…[4][5][6][7] Some have suggested that columellar struts or tip reconstruction may not be necessary if tip support mechanisms are not disrupted. 19 We have found that this is true only in very rare cases. The TIG technique, popularized by Kridel and Foda, establishes a strong connection between the septum and medial crura using suture to control tip rotation and projection.…”
Section: Discussionmentioning
confidence: 89%
“…[4][5][6][7] Some have suggested that columellar struts or tip reconstruction may not be necessary if tip support mechanisms are not disrupted. 19 We have found that this is true only in very rare cases. The TIG technique, popularized by Kridel and Foda, establishes a strong connection between the septum and medial crura using suture to control tip rotation and projection.…”
Section: Discussionmentioning
confidence: 89%
“…Columellar struts are used to define the dropped and bulbous tips in about 30% of cases, and it might have greater role in middle eastern rhinoplasty than in White rhinoplasty. 8 , 9 The transfixion stitch as described above, is needed in about 20% of cases to define the amorphous tip and forces the unyielding thick skin to collapse and obliterates the dead space preventing edema collection and later fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the article, the authors performed all rhinoplasty surgery by closed technique, and this is an advantage when there is the necessity to restore the natural support structures of the nose such as the paramedian and median support ligaments. We believe that it is not easy 1 We believe that our understanding of nasal tip support mechanisms is very much alike because they have also emphasized the importance of native support structures for nasal tip position and stability. We totally agree with their opinion about the utility of the columellar strut graft in closed rhinoplasty.…”
mentioning
confidence: 99%
“…Primary Open Approach Rhinoplasty" by Dr. Bitik et al The authors retrospectively analyzed a series of 100 consecutive primary rhinoplasty cases performed without the use of columellar strut grafts, to determine preoperative, morphed, and actual postoperative changes in nasal tip position. 1 Controlling and maintaining the position and shape of the nasal tip is one of the most important aspects of successful rhinoplasty. 2 In the article, the authors concluded that preoperative goals regarding nasal tip projection, nasal profile proportions, and columellar integrity could be consistently achieved without using columellar strut grafts.…”
mentioning
confidence: 99%
See 1 more Smart Citation